ANALISIS HAMBATAN IMPROVISASI BERWIRAUSAHA PADA USAHA KULINER DIKOTA PADANG - Astri Ghina; Adzra Helga Engrasia Gushendri (Pusat Riset dan Inovasi Nasional, 2022)
Micro, Small and Medium Enterprises (MSMEs) have a vital contribution to Indonesian economy. It is characterized by a large number which can accommodate a large number of workers. However, many MSMEs face many internal and external challenges in improvising their business. The purpose of this study is identifying challenges faced by MSMEs in terms of external aspects which include technological turbulence and market turbulence as well as internal aspects which include fear of failure, anxiety, disappointment, distress, and tension; and Qualitative methods with interview techniques are used to explore information from the experience of SMEs as resource persons who have been selected with certain criteria. The research’s findings show that the external barriers arise from limited knowledge and resources while the internal barriers of entrepreneurs arise from the personal lives and demands of business consumers. The research’s contribution is to provide facts for MSMEs to be used as a basis for evaluating business performance so that they can prepare corrective steps in improvising. In addition, the measuring instrument used as an interview protocol can be used as a reference for further study in similar topics.